Mechanistic study on the coupling reaction of CO2 with propylene oxide catalyzed by (CH3)4PI·MgCl2. Issue 14 (12th April 2022) - Ali, Jemal Mohamed; Mohammed, Ahmed Mustefa; Mekonnen, Yedilfana Setarge
Abstract: The mechanistic study of CO2 coupling with propylene oxide (PO) into cyclic carbonate catalyzed by (CH3 )4 PI has been investigated using the B3 LYP/6‐311++G (d, p)/B3 LYP/6‐31G (d) level of theory for non‐iodine atoms and LANL2DZ was used, together with its associated basis set for the iodine atom. Two hypothetical reaction mechanisms were proposed for the studied reaction and thermodynamic and kinetic parameters were computed for each step to determine the more favorable route. The density functional theory (DFT) study reveals that the reaction prefers to proceed through a three‐step mechanism (pathway II) than a tri‐molecular intermediate (pathway I) where the CO2 and the catalyst act simultaneously on the PO ring. The rate‐determining step of the catalytic reaction is found to be the ring‐opening step with an energy barrier of 27.1 kcal/mol (pathway II) in the gas phase, which is kinetically more favorable than that of non‐catalytic CO2 fixation with a relatively higher barrier of 63.7 kcal/mol. The synergetic effect of MgCl2 is tested as a cocatalyst for the (CH3 )4 PI/MgCl2 catalyzed reaction and it gave a better result and minimized the activation energy for the reaction and the rate‐determining step was the ring closure with the free energy of activation 18.8 kcal/mol in the gas phase. The polarizable continuum model was used to account for the solvent effect, obtaining the best results of 23.1 kcal/mol in water for pathway I and 16.5 kcal/mol and 14.9 kcal/mol in dimethyl sulfoxide for pathway II and binary system, respectively.